1994
DOI: 10.1128/aem.60.11.4022-4031.1994
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Iron-Oxidizing Microbial Mat Community Located near Aarhus, Denmark: Field Studies

Abstract: We investigated the microbial community that developed at an iron seep where anoxic groundwater containing up to 250 ,uM Fe2+ flowed out of a rock wall and dense, mat-like aggregations of ferric hydroxides formed at the oxic-anoxic interface. In situ analysis with oxygen microelectrodes revealed that the oxygen concentrations in the mat were rarely more than 50% of air saturation and that the oxygen penetration depth was quite variable, ranging from <0.05 cm to several centimeters. The bulk pH of the mat range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(117 citation statements)
references
References 45 publications
9
105
2
Order By: Relevance
“…The coexistence of IOB and IRB suggests a localized iron cycle as found in similar sharp redox environments (Emerson & Revsbech, 1994;Weiss et al, 2003). IOB activity in the GSI would be responsible for the suboxic deposition of ferric oxides, which remain poorly ordered, and reactive HFO because of interactions with bacterial extracellular polymers (Hanert, 2002;Sobolev & Roden, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…The coexistence of IOB and IRB suggests a localized iron cycle as found in similar sharp redox environments (Emerson & Revsbech, 1994;Weiss et al, 2003). IOB activity in the GSI would be responsible for the suboxic deposition of ferric oxides, which remain poorly ordered, and reactive HFO because of interactions with bacterial extracellular polymers (Hanert, 2002;Sobolev & Roden, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…The rod-like structure shown in Figs. 1b and 2a resembles the sheath of L. ochracea [2,6], while the distinctive helical structure in Figs. 1b and 2 resembles the stalk of G. ferruginea [7,24].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the fact that the latter are not known to reduce nitrate, the enrichment cultures obtained in this study did not contain morphotypes that formed conspicuous appendices or ¢lamentous sheaths [6,7] ; the cells were morphologically inconspicuous short rods. Also Emerson and Revsbech [10] have reported that in the mat-like aggregations of ferric hydroxides of an iron seep, the major populations of bacteria responsible for aerobic iron oxidation were not Gallionella or Leptothrix species, but unicellular, morphologically inconspicuous, unidenti¢ed bacteria. Emerson and Moyer [11] isolated and characterized several pure cultures of rodshaped, aerobic, iron-oxidizing bacteria from groundwater samples that were only distantly related to the classical iron oxidizers.…”
Section: Ferrous Iron Oxidation By Denitrifying Bacteriamentioning
confidence: 99%
“…The stalked bacterium Gallionella ferruginea and sheathed bacteria belonging to the genus Leptothrix are the classical examples of bacteria catalyzing the aerobic oxidation of ferrous iron at neutral pH [6^8], although the biochemical basis of the iron-oxidizing activity has been substantiated only in a few cases [9]. A more recent study of an iron-oxidizing microbial mat showed that the majority of the microbial community consisted of nonappendaged, unicellular bacteria intimately associated with the iron oxides [10]. The recent isolation from groundwater of novel, rod-shaped, aerobic, iron-oxidizing strains of neutrophilic bacteria which are only distantly related to the classical iron oxidizers indicates that there might actually be a wide variety of microorganisms capable of this metabolism [11].…”
Section: Introductionmentioning
confidence: 99%